MTsS Kluet Utara Aceh Selatan تحسين اللهجة اللغوية باستخدام وسيلة فيديو بـ - Amaliah, Zarinatul; Idris, Aisyah; Fajriah, Fajriah (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2022)
Based on the result of the  observation in grade 1 at MTsS Kluet Utara, the researcher found that the majority of the students were difficult to communicate in Arabic language. The difficulties are  not only  about the pronounciations but also Arabic alphabets, words, and sentences. In fact, they speak Arabic by using the Indonesian dialect. The aims of this study were to know  the effectiveness of the video media used to improve students’ Arabic dialect. This observation is also to know the activities of  the teachers  and  the students in the implementation of the video media. The researcher applied the  pre-experimental method  through  one group pre -test post –test design.   To collect the data, the researcher used the observation sheets and provided pre and post-tests to the students. The findings of the study were that the T-test was higher than T-table (4,20 <2,07<2,78). Furthermore, the observation showed  that the teachers’ activities in using the video to improve the language dialect were very good scores (88%) after the implementation of the media. In accordance with the teachers, the students’ achievement  were also very good (85%).